The Limits of Market Discipline in Reducing Banks' Risk Taking - Jürg Blum (Swiss National Bank, Study Center Gerzensee, 2000)
This paper analyzes the influence of market discipline on the risk-taking incentives of banks. It is shown that market discipline reduces risk if banks can credibly commit to a given level of risk before the interest rate on deposits is set. If, however, the bank can readjust the level of risk after the deposit rate is contracted, market discipline leads to an increase in risk. The reason is that rational depositors anticipate the banks' behavior and therefore ask for a higher risk premium ex ante. Facing a higher interest burden, the banks in turn have an even greater incentive to increase risk becouse the option to go bankrupt is more valuable.
Keywords: G21; G28; 330; Market discipline; banks; risk taking; deposit insurance; Bank; Risikomanagement; Einlagensicherung; Theorie